Choice by iterative search - Daisuke Nakajima; Yusufcan Masatlioglu (Theoretical Economics, 2013)
When making choices, decision makers often either lack information about alternatives or lack the cognitive capacity to analyze every alternative. To capture these situations, we formulate a framework to study behavioral search by utilizing the idea of consideration sets. Consumers engage in a dynamic search process. At each stage, they consider only those options in the current consideration set. We provide behavioral postulates characterizing this model. We illustrate how one can identify both search paths and preferences.
Keywords: D11; D81; 330; Search; satisficing; bounded rationality; consideration set; reference-dependent choice; revealed preference